Research on Active Control of X-Type Interconnected Hydropneumatic Suspensions for Heavy-Duty Special Vehicles via Extended State Observer-Model Predictive Control - Geqiang Li; Yuze Yan; Yuchang Liu; Shuai Wang (Applied Sciences)
To address the weak adaptability of the passive X-type interconnection hydropneumatic suspension to different road surfaces and the poor performance of traditional single-control methods, an active controller based on the extended state observer (ESO) and model predictive control (MPC) was designed for the X-type interconnection hydropneumatic suspension of heavy-duty special vehicles. First, the structure of the X-type interconnection hydropneumatic suspension was analyzed. A three-degree-of-freedom (DOF) linearized hydropneumatic suspension model with disturbances was established based of the seven-DOF full-vehicle model of the active X-type interconnection hydropneumatic suspension. The disturbances were analyzed, and a disturbance ESO was developed. A controller for MPC was subsequently designed based on the linearized state space model, forming a controller for ESO-MPC. Simulations were conducted on both C-class random roads and convex pavement, with fuzzy PID control included for comparison. The simulation results demonstrated that, compared with the passive X-type interconnection hydropneumatic suspension, the active suspension with the controller for ESO-MPC achieved reductions in body vertical acceleration, pitch angular acceleration, and roll angular acceleration of 18.7%, 24.7%, and 26.1%, respectively, on Class C random roads. With fuzzy PID control, the reductions were 5.59%, 7.99%, and 15.54%, respectively. For convex pavement, the controller for ESO-MPC reduced body vertical acceleration, pitch angular acceleration, and roll angular acceleration by 36.5%, 21.2%, and 18.1%, respectively, whereas fuzzy PID control resulted in reductions of 14.04%, 10.6%, and 7.92%, respectively. Compared with fuzzy PID control, the controller for ESO-MPC significantly improved the performance of the hydropneumatic suspension system, achieving precise control of the X-type interconnection hydropneumatic suspension system for heavy-duty special vehicles, thereby enhancing ride comfort and stability.